The Use of Repetitive Structures among Malaysians - Nadarajan, Shanthi (Language Society and Culture, University of Tasmania, Australia, 2007)
This paper examines the complexities of using English in a bilingual context. It looks at some common forms of repetitions and reduplications that exist among speakers of the Malay and Tamil languages in Malaysia which is easily transferred into their English discourse. While most proficient speakers of English generally recognize it as awkward and inaccurate word use, the message is generally understood and accepted due to the cross cultural mix of the society. Less proficient speakers are either unaware of the awkward structure or ambivalent to its usage. The first part of the article sets out to investigate the various forms of reduplications that exist in Malay and Tamil and how such forms are used in the learners’ discourse. The second part explains the semantic and syntactical organization that enables such forms to be repeated meaningfully. It further explores the reasons for people wanting to retain such repetitive structures despite realizing its inaccurateness and calls for some level of flexibility in the way English should be used in second language environments. The article has implications for both bilingual education and socio cultural identities.